Nanoparticle-based drug delivery systems to enhance cancer immunotherapy in solid tumors - Zhang, Jiaxin; Wang, Siyuan; Zhang, Daidi; He, Xin; Wang, Xue; Han, Huiqiong; Qin, Yanru (Frontiers in Immunology, 2023)
Immunotherapy has developed rapidly in solid tumors, especially in the areas of blocking inhibitory immune checkpoints and adoptive T-cell transfer for immune regulation. Many patients benefit from immunotherapy. However, the response rate of immunotherapy in the overall population are relatively low, which depends on the characteristics of the tumor and individualized patient differences. Moreover, the occurrence of drug resistance and adverse reactions largely limit the development of immunotherapy. Recently, the emergence of nanodrug delivery systems (NDDS) seems to improve the efficacy of immunotherapy by encapsulating drug carriers in nanoparticles to precisely reach the tumor site with high stability and biocompatibility, prolonging the drug cycle of action and greatly reducing the occurrence of toxic side effects. In this paper, we mainly review the advantages of NDDS and the mechanisms that enhance conventional immunotherapy in solid tumors and summarize the recent advances in NDDS-based therapeutic strategies, which will provide valuable ideas for the development of novel tumor immunotherapy regimen.